MRI of the cervical nerve roots in the diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy: a single-institution, retrospective case–control study - Toshihiko Suenaga; Kanta Tanaka; Nobuyuki Mori; Yusuke Yokota (BMJ Open)
Objective To systematically evaluate the usefulness of assessing the cervical nerve roots by MRI for the diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP).Design Single-institution, retrospective case–control study.Setting A regional referral hospital.Participants We retrospectively enrolled 15 consecutive patients with CIDP who satisfied the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) typical and definite criteria and underwent cervical MRI. 30 control patients who had also undergone cervical MRI were included, matched with regard to sex, age and MRI system. The diagnoses of the control patients included cervical spondylosis (n=19), cervical spine trauma (n=2), infection (n=1), malignancies (n=4), demyelinating disorders (n=2) and neurodegenerative disorders (n=2).Measurement A radiologist determined the C5–C8 root diameters on the coronal short tau inversion recovery (STIR) images. Signal intensities of these roots were quantified as nerve-to-muscle contrast-to-noise ratios (CNRs), which were calculated using mean signal intensities of the roots and sternocleidomastoid muscle as well as SD of background noise. Statistical analyses were performed to determine the diagnostic accuracy of the diameters and nerve-to-muscle CNRs. Another radiologist reviewed MRI for ensuring reproducibility.Results The root diameters showed no significant differences between the patients with CIDP and control patients. The nerve-to-muscle CNRs were significantly higher in the patients with CIDP. We defined the sum of nerve-to-muscle CNRs of C5–C8 roots as the CNR score to serve as an index of overall signal intensity. The area under the receiver operating characteristic curve of CNR scores was 0.731. The reproducibility of the assessment procedure was satisfactory.Conclusions Our results suggest that assessment of the cervical nerve roots by MRI is useful for CIDP diagnosis when the signal intensities, rather than the diameters, are paid more attention on STIR images.